University training in Public Administration and bureaucratic capacities in Argentina (1990-2017) (2019)
This work aims to reflect on the link between the bureaucratic capacities probably involved in the management of States that are recognized in two currents: neoliberal and neo-developmentalist and the development of the training offer in Administration and Public Management in Argentina during the last twenty-seven years, from questioning ourselves: what would be those capacities in each case? And what training offers would feed those capabilities? The work postulates that this training field is defined by the promises regarding their graduation profiles and the scope for them designed, at the same time that it is constituted as an institutionally consolidated horizon for the formation of state bureaucracies.